Bangladesh : Staff Report for the 2005 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion, Extension of the Arrangement, and Rephasing. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2005 Article IV Consultation highlights that since the last Article IV Consultation, Bangladesh's economy has continued to expand, supported by a stable macroeconomic environment and progress in implementing structural reforms, broadly in line with the recommendations made by the IMF Executive Board. Good progress has been made in strengthening the banking system. Bangladesh Bank has raised minimum capital requirements, taken steps to reduce insider lending, and improved the institutional framework for the prudential supervision of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet